Questioning Shariah bank loyalty: Do the roles of service quality and perceived fairness vary for the Bugis-Makassar ethnic? - Basalamah, M. Ridwan; Mawardi, Moh. Cholid (University of Islam Malang, 2022)
Bugis-Makassar ethnic group is known for its loyalty. There is a famous proverb, polo pang polo panni, which means the readiness of individuals to sacrifice anything to obey and be loyal to the commitments made even if they have to break their thighs and wings. Unfortunately, limited studies are exploring the antecedents of loyalty by using cultural and gender differences perspectives. This is surprising because if gender and ethnic background are genuinely exclusive, they would need a different selling, marketing, and loyalty strategy. This study aimed to fill the gap by empirically exploring the dimensions of service quality and perceived fairness on loyalty in the Sharia Bank of Indonesia. Through a questionnaire survey, 576 Bugis-Makassar were studied for this work. The questionnaire was employed based on the previous studies to establish the content validity of the study. Regression analysis is conducted to test the hypothesis. Our study shows that while service quality was found to be a significant predictor of loyalty in the Shariah bank, perceived fairness failed to affect loyalty. Despite their strong belief in Bugis-Makassar culture and philosophy, they tend to be more realistic when making buying decisions.